The prognostic importance of e-cadherin and p53 gene expression in transitional bladder carcinoma patients - Arısan, Serdar; Çaşkurlu, Turhan; Güney, Soner; Sönmez, Nurettin Cem; Keleş, Bayram; Ergenekon, Erbil; ARISAN, ELİF DAMLA (Kluwer Academic Publishers, 2005)
Objective: The clinical course of transitional cell carcinoma is highly variable. The determination of sensitive prognostic factors for transitional cell carcinoma is very important. Therefore e-cadherin and p53 immunohistochemical activity can be used with other prognostic factors. Methods: The study comprised with 61 (4 women and 57 men) selected patients who had transitional cell carcinoma. Paraffin embedded tissue sections were investigated immunohistochemically for e-cadherin normal staining and p53 over expression. Results: It is seen that when grade and stages of illness increased normal staining of e-cadherin decreased and p53 over expressed. Abnormal e-cadherin was significantly associated with disease recurrence (P < 0.001), disease progression (P < 0.001) and bladder specific survival. p53 differentiation was not significant for disease recurrence (P > 0.05) inverse to prognosis of illness. Transurethral resectomy and BCG treatments were not effected e-cadherin and p53 activity within the groups statistically. Conclusion: Significant differences can be helpful to investigate patients more detailed pathologically. These expression rates in different type of transitional cell carcinoma patients may represent a biologically more aggressive cancer, requiring early definitive therapy. This hypothesis should be evaluated in larger studies and prospective clinical trials.
Keywords: E-cadherins; Immunohistochemistry; p53; Prognosis; TCC; Tumor markers